If f (x) = x + 7, g(x) = 2x - 5, and h(x) = 2x + 4, then what is f(x) + h(x)*g(x) - 12?

1 Answer | Add Yours

thilina-g's profile pic

thilina-g | College Teacher | (Level 1) Educator

Posted on

`f(x) = x+7`

`g(x) = 2x-5`

`h(x) = 2x+4`

What you have asked is just the simple arithmetic involved with functions.

`f(x) + h(x) xx g(x) - 12`

`= (x+7)+(2x+4)xx(2x-5) - 12`

`=x+7 + (4x^2-10x+8x-20)-12`

`= x+7 + 4x^2-2x-20-12`

`= 4x^2-x -25`

 

Therefore,

`f(x) + h(x) xx g(x) - 12 = 4x^2-x -25`

 

 

 

We’ve answered 318,951 questions. We can answer yours, too.

Ask a question